Collision and injury criteria when working with collaborative robots - Human Science Group, Buxton (London, 2012)
"There is a need for adequate protection of people from the health and safety risks associated with collaborative robot systems. Standard ISO 10218 (Parts 1 and 2) and a draft Technical Specification TS 15066 'Collaborative robots' have been developed to deal specifically with this situation. This study explored the safety, reliability and evidence for the force limits defined by the draft TS 15066, and of the methods for testing them. It also addressed whether the proposed approach in the draft TS 15066 is likely to adequately protect people from the risks. Risk assessment of potential collision scenarios, human reliability and behaviour issues, and equipment failure modes and rates are discussed, as is the adequacy of personal protective equipment against collision injuries. Collaborative robots is an subject area that is still growing. This report and the work it describes were funded by the Health and Safety Executive (HSE). Its contents, including any opinions and/or conclusions expressed, are those of the authors alone and do not necessarily reflect HSE policy."